Safety, pharmacokinetics and pharmacodynamics of the anti‐hepcidin Spiegelmer lexaptepid pegol in healthy subjects. (8th April 2016) - Boyce, M; Warrington, S; Cortezi, B; Zöllner, S; Vauléon, S; Swinkels, D W; Summo, L; Schwoebel, F; Riecke, K
Abstract : Background and Purpose: Anaemia of chronic disease is characterized by impaired erythropoiesis due to functional iron deficiency, often caused by excessive hepcidin. Lexaptepid pegol, a pegylated structuredl ‐oligoribonucleotide, binds and inactivates hepcidin. Experimental Approach: We conducted a placebo‐controlled study on the safety, pharmacokinetics and pharmacodynamics of lexaptepid after single and repeated i.v. and s.c. administration to 64 healthy subjects at doses from 0.3 to 4.8 mg·kg −1 . Key Results: After treatment with lexaptepid, serum iron concentration and transferrin increased dose‐dependently. Iron increased from approximately 20 μmol·L −1 at baseline by 67% at 8 h after i.v. infusion of 1.2 mg·kg −1 lexaptepid. The pharmacokinetics showed dose‐proportional increases in peak plasma concentrations and moderately over‐proportional increases in systemic exposure. Lexaptepid had no effect on hepcidin production or anti‐drug antibodies. Treatment with lexaptepid was generally safe and well tolerated, with mild and transient transaminase increases at doses ≥2.4 mg·kg −1 and with local injection site reactions after s.c. but not after i.v. administration. Conclusions and Implications: Lexaptepid pegol inhibited hepcidin and dose‐dependently raised serum iron and transferrin saturation. The compound is being further developed to treat anaemia of chronic disease.